2014
DOI: 10.3747/pdi.2012.00257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Modality Choice on Rates of Hospitalization in Patients Eligible for Both Peritoneal Dialysis and Hemodialysis

Abstract: ♦ Background: Hospitalization rates are a relevant consideration when choosing or recommending a dialysis modality. Previous comparisons of peritoneal dialysis (PD) and hemodialysis (HD) have not been restricted to individuals who were eligible for both therapies. ♦ Methods: We conducted a multicenter prospective cohort study of people 18 years of age and older who were eligible for both PD and HD, and who started outpatient dialysis between 2007 and 2010 in four Canadian dialysis programs. Zero-inflated negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…In a more recent study, Quinn et al, in an effort to reduce bias, assessed the impact of dialysis modality on hospitalization rates of patients who were classified as eligible for both therapies in a multicenter prospective Canadian cohort. While no overall difference in hospitalization rates was found, there was a significant increase in hospitalization rates with HD when the population was further restricted to those initiating outpatient dialysis after at least 4 months of pre‐dialysis care . Of note, most hospital admissions (>75%) were unrelated to dialysis.…”
Section: Dialysis Modalities and Outcomes: Moving Beyond Survivalmentioning
confidence: 89%
See 1 more Smart Citation
“…In a more recent study, Quinn et al, in an effort to reduce bias, assessed the impact of dialysis modality on hospitalization rates of patients who were classified as eligible for both therapies in a multicenter prospective Canadian cohort. While no overall difference in hospitalization rates was found, there was a significant increase in hospitalization rates with HD when the population was further restricted to those initiating outpatient dialysis after at least 4 months of pre‐dialysis care . Of note, most hospital admissions (>75%) were unrelated to dialysis.…”
Section: Dialysis Modalities and Outcomes: Moving Beyond Survivalmentioning
confidence: 89%
“…While no overall difference in hospitalization rates was found, there was a significant increase in hospitalization rates with HD when the population was further restricted to those initiating outpatient dialysis after at least 4 months of pre-dialysis care. 60 Of note, most hospital admissions (>75%) were unrelated to dialysis.…”
Section: Hospitalizationmentioning
confidence: 99%
“…CKD affects approximately 10% of the adult population and is associated with increased morbidity and mortality (1)(2)(3)(4)(5). Prior studies have also observed high resource use among patients with CKD (6)(7)(8)(9). The majority of these studies have focused on either inpatient use or emergency department (ED) use among patients with ESRD (8,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have also observed high resource use among patients with CKD (6)(7)(8)(9). The majority of these studies have focused on either inpatient use or emergency department (ED) use among patients with ESRD (8,(10)(11)(12)(13). There has been limited exploration of how patients with CKD use the ED and whether utilization is associated with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies were identified, suggesting that CV event-related hospitalisation rates account for ≈ 20% of all hospitalisations in dialysis cohorts. [108][109][110] The most relevant source of evidence to the UK RRT population reported that CV events made up 17.6% of the annual inpatient event rate in a cohort of 1226 UK HD patients. 110 This value was applied in the base case.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%